2004
DOI: 10.1002/jtra.10052
|View full text |Cite
|
Sign up to set email alerts
|

Lead intoxication: Histological and oxidative damage in rat cerebrum and cerebellum

Abstract: The present experiment was designed to study the neurotoxic consequences of lead exposure on antioxidant enzymes like glutathione, glutathione peroxidase, super oxide dismustase, and catalase along with structural changes both in cerebrum as well as cerebellum. Lead was administrated orally in the doses of 50 mg/kg for a period of 8 weeks and study was performed at the end of exposure. Decrease in the concentration of all the antioxidant enzymes was observed, and after lead treatment, transverse sections of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
36
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 30 publications
9
36
0
Order By: Relevance
“…Many animal studies have shown that lead is capable of causing oxidative stress in the kidney, liver, and brain (Ercal et al, 1996;Patra et al, 2001). The absorbed Pb is conjugated in the liver and passed to the kidney, where a small quantity is excreted in urine and the rest accumulates in various body organs, affecting and affects many biological activities at the molecular, cellular and intercellular levels, which may result in morphological alterations that can remain even after Pb levels have fallen (Jarrar, 2003;Sidhu & Nehru, 2004;Taib et al, 2004;Flora et al, 2006). The kidney is a sensitive target organ for lead exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Many animal studies have shown that lead is capable of causing oxidative stress in the kidney, liver, and brain (Ercal et al, 1996;Patra et al, 2001). The absorbed Pb is conjugated in the liver and passed to the kidney, where a small quantity is excreted in urine and the rest accumulates in various body organs, affecting and affects many biological activities at the molecular, cellular and intercellular levels, which may result in morphological alterations that can remain even after Pb levels have fallen (Jarrar, 2003;Sidhu & Nehru, 2004;Taib et al, 2004;Flora et al, 2006). The kidney is a sensitive target organ for lead exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that lead damages the nerve cells as well as ganglia and also alters the cell structure causing cerebral edema, and focal cerebellar atrophy and neuronal degeneration as a result of lead encephalopathy in rat brain [69] . Treatment with omega-3FA has been found to restore cellular functions, reduce oxidative stress and inflammation, repair cellular damage and mitigate the activation of apoptotic processes after traumatic brain injury in human [71] .…”
Section: Doi: 101159/000481808mentioning
confidence: 99%
“…Exposure to lead in rats affects the normal histological structure of the brain and causes disturbances in the normal functions performed by it. Lead toxicity also damages the nerve cells and ganglia linked with the damage of cellular structure as well as the neuronal degeneration as a result of lead encephalopathy in rat brain [69,70] .…”
Section: Doi: 101159/000481808mentioning
confidence: 99%
“…[4] This affects many biological activities at the molecular, cellular and intercellular levels, which may result in morphological alterations that can remain even after lead level has fallen. [5,6,7,8] Lead element is one of the most common toxic metal and affects all organs of the body including liver. Liver is the largest organ in the body and it is located in the upper three regions in the abdomen.…”
Section: Introductionmentioning
confidence: 99%